Revisiting Turkmen and Javanese Folktales: Exploring Educational and Character-Building Values - Tazegul Nyyazmammedova (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
Folktales are a medium rich in educational values and play a vital role in character formation and cultural preservation. This study examines the educational and cultural values found in selected folktales from Turkmenistan and Java, highlighting stories such as Yartykulak, Gorogly, Dede Korkut, Gul-Bilbil, Gul-Senuber from Turkmenistan and their parallels in Javanese folktales such as Kancil, Rara Jonggrang, Ande-Ande Lumut, Panji Asmarabangun, and Buto Ijo. The literature and textual analysis show that folktales are not merely a form of entertainment, but also a repository of moral wisdom—conveying values such as bravery, cleverness, loyalty, justice, perseverance, and respect. Using a descriptive qualitative approach, this study identifies shared and distinct values reflected in the characters, conflicts, and resolutions within each story. The findings indicate that both Turkmen and Javanese folktales carry important lessons on social responsibility, heroism, cultural identity, and ethical behavior. These stories are thus valuable tools for character education, particularly in multicultural and cross-cultural learning settings. Moreover, the study recommends the integration of folktales into character education curricula and the use of digital storytelling platforms to engage younger generations. Preserving and promoting folktales in both traditional and digital formats is crucial to ensuring the transmission of moral and cultural values, fostering an ethical, empathetic, and culturally rooted generation in an increasingly globalized world.